Sero-Prevelance Of Anti Sars-Cov-2 Antibodies With Impact Of Age, Gender And Severity Of The Disease: A Hospital Based Study: COVID-19 - Khan, Hamzullah; Khalid, Muhammad; Khan, Khalid; Masood, Adnan (ADVANCES IN BASIC MEDICAL SCIENCES, 2021)
Objectives: To determine the sero-prevelance of neutralizing antibodies levels against SARS-COV 2 with impact of age, gender and severity of the disease. Methodology: A cross sectional study was conducted in department of Pathology from 1st July 2020 to 15th August 2020. A total of 109 respondents attended the laboratory for knowing their anti SARS-COV-2 antibodies levels irrespective of age and gender. Antibodies levels were measured by electro-chemiluminescence immunoassay using Roche Cobas E411 Chemistry Analyzer. Results: The mean age of the subjects was 35+13 years while mean cut off antibodies levels of patients with standard deviation was 15.74+7.18. Out of total, 82(75.2%) were males and 27(24.8%) were females. 91(83.5%) of the respondents were in age below 60 years and 18 (16.6%) were above 60 years. The mean antibodies level were higher in patients with age < 60 y and in patients who had symptoms in the recent past during the pandemic (17.5+3.93,p=0.03) and (36.51+4.41, p=0.001) respectively. Similarly a statistically significant inverse correlation was observed between antibodies levels and age of patients (p=0.03, r=-0.204). Among the asymptomatic/mildly symptomatic patients, 10/67, had yielded antibodies with a seroprevelance of 14.9% while all PCR positive cases (100%) recovered from COVID-19 had developed antibodies after 3 week of being reported negative. Conclusion: A low mean neutralizing antibodies levels production against SARS-COV-2 had a sero-prevelance of 14.9% in asymptomatic non-PCR-tested population. All positive patients who recovered had developed antibodies after 3 weeks of being reported negative. Age<60 years, female and patients who had symptoms matching the COVID-19 during the pandemic irrespective of their viral profile produces higher level of antibodies. Male gender and patients with age>60y showed low levels of antibodies. Key words: COVID-19, Pandemic, Anti SARS-COV-2 antibodies.